THE EFFECT OF ENTERPRISE RISK MANAGEMENT, KNOWLEDGE MANAGEMENT, AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL RESILIENCE - Zef Arfiansyah (International Journal of Contemporary Accounting, 2021)
This study aims to identify the influence of Enterprise Risk Management, Knowledge Management, and Organizational Culture on the company's ability to survive in an ever-changing environment. This research is a quantitative study using primary data. The data were obtained through a questionnaire distributed to accountants who held the lowest supervisory positions in private Indonesian companies. With a sample of 103 respondents, the data were processed using linear regression. This study found that in the context of companies in Indonesia, Enterprise Risk Management and Organizational Culture can increase Organizational Resilience. However, this study failed to prove the role of Knowledge Management in Organizational Resilience. This study provides contributions in both managerial and theoretical aspects. In the managerial aspect, this study implies ERM and organization culture are elements that should be implemented so that companies can survive in a volatile environment. From a theoretical point of view, this research has proven that in the long term ERM is able to maintain organizational resilience. Besides, this study also indicates that knowledge management is still not widely applied by companies in Indonesia. For this reason, the attention of management so that knowledge management is applied needs to be improved.